Charge compensation engineering for high-performance dolomite-type BaTi(BO3)2:Eu3+ red-emitting phosphor for backlight display applications with a wide color gamut. Issue 7 (2nd February 2022) - Yu, Bin; Chen, Jiale; Sun, Minghao; Chen, Nianmin; Li, Yuchan; Wang, Yunjian
Abstract : The luminescent properties of BaTi(BO3 )2 :Eu 3+ red phosphor were significantly improved by utilizing the charge compensation of the alkali metal Na + ion, and a wide color gamut pc-WLED was successfully prepared using the BaTi(BO3 )2 :Eu 3+, Na + phosphor. Abstract : Exploiting high color purity phosphors is a core problem in the development of phosphor conversion light-emitting diodes (pc-LEDs) for display devices. Eu 3+ -activated BaTi(BO3 )2 (BTB) red-emitting phosphors were first synthesized via a solid-state reaction at low temperature and alkali metal ions Na + were co-doped in BTB: x Eu 3+ to improve the luminescence properties. The occupation of the Eu 3+ ions and the enhancement principles of the Na + ions and their effect on the photoluminescence properties of the BTB: x Eu 3+ phosphors are discussed in detail. The BTB: x Eu 3+, Na + system demonstrated a strong thermal stability (68.4% at 150 °C), low color temperature (about 1940–1950 K) and high color purity (almost 90%). Furthermore, the prototype LED device can emit a bright white light, has a stable luminous efficiency and color rendering index, and the color gamut reaches 115.5% of the NTSC standard. Therefore, the BTB: x Eu 3+, Na + series phosphors provide a better choice for the development of lighting and display devices with a wide color gamut.